Avaliação da atenção concentrada e memória em tabagistas com baixa carga tabágica - Manzano, Roberta Munhoz; Ambrozin, Alexandre Ricardo Pepe [UNESP]; Ruiz, Nara Silveira; Carletti, Carla de Oliveira; Ramirez, Ariane Pereira; Spigolon, Neilson Spigolon Giedri Palmieri; Oliveira, Luiz Carlos; Belancieri, Maria de Fátima (My University, 2013)
Introduction: Smoking is considered by World Health Organisation (WHO) a disease, since nicotine is addictive and cause physical, emotional and behavioral disorders in people who smoke. The objective of this study was to evaluate the concentrated attention and memory in smokers and nonsmokers, and the influence of one cigarette in this variables. Material and Methods: We selected two groups of subjects between 18 and 25 years, with no history of acute or chronic respiratory disease. Group 1 (G1) consist of 40 nonsmoking individuals and group 2 (G2) 40 smokers (who smoked less than 20 cigarettes per day, for up to 10 years). The subjects were tested for concentrated attention and memory test (AC Test), nonsmokers performed the test once, smokers performed the test twice, before smoking and after five minutes after smoking one cigarette. Smokers stayed without cigarret for one our before the first test. Results: Comparing the tests nonsmokers versus smokers first test, there was no significant difference (p> 0.05), however, the analysis of the two trials of smokers, showed improvement in concentrated attention and memory after smoke (p <0.0001). Conclusions: There was no difference in Concentrated Attention and Memory among nonsmokers and smokers in abstinence, however smokers showed significant improvement in AC Test after smoking.

Introdução: O tabagismo é considerado pela Organização Mundial de Saúde (OMS) uma doença, uma vez que a nicotina causa dependência e provoca alterações físicas, emocionais e comportamentais na pessoa que fuma. Diante disso o objetivo deste trabalho foi avaliar a atenção concentrada e memória em tabagistas e não tabagistas, bem como a utiliza- ção e a influência de um cigarro sobre esta. Material e Métodos: Foram selecionados 80 indivíduos com idade entre 18 e 25 anos, sem história de doença respiratória aguda ou crônica, divididos em dois grupos, sendo grupo 1 (G1) composto por não tabagistas (40 indivíduos) e o grupo 2 (G2) por tabagistas que fumavam menos de 20 cigarros por dia, por no máximo 10 anos (40 indivíduos). Os sujeitos foram submetidos ao teste de atenção concentrada e memória (Teste AC), sendo que os tabagistas realizaram o teste, antes e cinco minutos após fumar um cigarro. Foi solicitado aos tabagistas que ficassem uma hora sem fumar, antes da realização do primeiro teste. Resultados: Comparando o resultado do teste dos não tabagistas com o teste dos tabagista, não houve diferença significativa entre eles (p>0,05). Já comparando os dois testes antes e após a inalação de um cigarro nos indivíduos tabagistas, houve melhora no Teste AC (p<0,0001). Conclusões: Não houve alteração significativa na Atenção Concentrada e Memória entre os não tabagistas e os tabagistas em abstinência, entretanto os tabagistas apresentaram melhora significativa do Teste AC.
Evaluation of concentrated attention and memory in smokers with low level of nicotin